Risk identification and evaluation of customer collaboration in product development - Xuefeng Zhang; Yu Yang; Jiafu Su (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this paper is to identify risk factors that caused by customer collaboration in new product development systematically, and propose an approach to judge which risk factors are critical and catch substantial attention. Design/methodology/approach: This study identifies risk factors according to the results of case studies of enterprises in china. On this basis, an improved rough number approach is put forward to evaluate the importance of risk factors. Findings: Firstly, classify risk factors into three aspects. Then, present a risk factor set, which include thirty-seven risk factors. At last, determine which risk factors are critical by using an improved rough number approach. Originality/value: Considering there are few researches studying comprehensive risk factors of customer collaboration and assessing them, this paper explores a risk factor set of customer collaboration in product development stage, and proposes a novel approach, which can help to solve the problem of subjective, vague and lack of prior information of evaluation, to evaluate risk factors.
Keywords: 650; customer collaboration; product development; risk identification; risk evaluation; improved rough number